Global agricultural market trends revisited: The roles of energy prices and biofuel production - Harald von Witzke; Steffen Noleppa; Gerald Schwarz (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2009)
This paper has benefited greatly from a discussion of an earlier version with the participants of the first Humboldt Forum for Food and Agriculture in Davos, Switzerland in March 2009. Research has been made possible in part by a research grant from BASF SE - The Chemical Company. The first two sections of the paper draw on von Witzke et al. (2008) who provide a detailed discussion of the Agricultural Treadmill and its end.
Keywords: 330